Nurse Therapeutic Communication Relationship with Parental Anxiety Levels which Preschoolers Undergo Hospitalization in the Lima Ranap Room Mitra Plumbon Hospital - Musyarofah, Musyarofah; Fajrin Kurniawan, Fakhri (Jurnal Medisci, 2023)
Problems that generally affect the level of anxiety of parents whose preschoolers undergo hospitalization are divided into two objects, internal factors including: (1) Age factors owned by parents; (2) Sex differences of parents; and (3) Traumatic fears felt by parents. While from the external include: (1) The level of education of parents is quite low; and (2) Parents' knowledge of children's health is still low. One indicator in lowering the anxiety level of the patient's parents is therapeutic communication skills. In general, the purpose of this study was to determine the relationship between nurses' therapeutic communication with the level of parental anxiety due to hospitalization in preschool-aged children at Ranap Lima Mitra Plumbon Hospital. This study uses quantitative research with a cross-sectional approach and uses correlation or correlational research methods. The population in this study was all parents of patients whose preschool-aged children underwent hospitalization in Ranap Room Five of Mitra Plumbon Hospital. The sampling technique uses accidental sampling method based on chance. In terms of this sampling, researchers conducted a study for one month, where the sample obtained was 28 respondents.